Takayasu Arteritis: A current perspective on diagnosis and emerging treatments - Nicole Nitschke; Martyna Mocarska; Anna Orłowska; Katarzyna Strakowska; Laura Opalska; Anna Maryńczak; Adrianna Muciek; Jan Mencel; Marta Lenar; Filip Lenar (Quality in Sport, 2025)
Takayasu-Arteritis (TA), also known as the pulseless disease or aortic arch syndrome is a rare but serious condition that primarily affects mainly the large blood vessels. This inflammatory vascular disease is characterised by intimal fibrosis and vessel narrowing, especially affecting the aorta, its branches and the pulmonary arteries. Patients typically present asymptomatic but such conditions as weak or absent pulses in arms or legs, angina pectoris and stroke-like symptoms can appear in severe cases.